Predictors for success and failure in international medical graduates: a systematic review of observational studies - Inge Schabort; Meisam Abdar Esfahani; Rachel Couban; Nia Wyn Roberts; Carl Heneghan; Neha Arora; Vahid Ashoorion (BMC Medical Education, 2024)
Abstract Background International Medical Graduates (IMG) are an essential part of the international physician workforce, and exploring the predictors of success and failure for IMGs could help inform international and national physician labour workforce selection and planning. The objective of this study was to explore predictors for success for selection of IMGs into high stakes postgraduate training positions and practice and not necessarily for informing IMGs. Methods We searched 11 databases, including Medline, Embase and LILACS, from inception to February 2022 for studies that explored the predictors of success and failure in IMGs. We reported baseline probability, effect size in relative risk (RR), odds ratio (OR) or hazard ratio (HR) and absolute probability change for success and failure across six groups of outcomes, including success in qualifying exams, or certificate exams, successful matching into residency, retention in practice, disciplinary actions, and outcomes of IMG clinical practice. Results Twenty-five studies (375,549 participants) reported the association of 93 predictors of success and failure for IMGs. Female sex, English fluency, graduation recency, higher scores in USMLE step 2 and participation in a skill assessment program were associated with success in qualifying exams. Female sex, English fluency, previous internship and results of qualifying exams were associated with success in certification exams. Retention to work in Canada was associated with several factors, including male sex, graduating within the past five years, and completing residency over fellowships. In the UK, IMGs and candidates who attempted PLAB part 1, ≥ 4 times vs. first attempters, and candidates who attempted PLAB part 2, ≥ 3 times vs. first attempters were more likely to be censured in future practice. Patients treated by IMGs had significantly lower mortalities than those treated by US graduates, and patients of IMGs had lower mortalities [OR: 0.82 (95% CI: 0.62, 0.99)] than patients of US citizens who trained abroad. Conclusions This study informed factors associated with the success and failure of IMGs and is the first systematic review on this topic, which can inform IMG selection and future studies. Systematic review registration PROSPERO: CRD42021252678.